The elements of learning - Banner, James M., Jr., 1935-; Cannon, Harold C., 1930- (New Haven, Conn. : Yale University Press, 1999)
Banner and Cannon combine such elements of learning as industry, enthusiasm, pleasure, imagination, and cooperation with circumstances of learning such as who teaches you and how you learn to create a model for the qualities involved in being a student.
The adventure of learning -- pt. 1. The elements of learning. Industry : Working on your weaknesses ; Why teachers work you so hard -- Enthusiasm : Learning in spite of a bad teacher -- Pleasure : Delayed gratification -- Curiosity : What is knowledge? -- Aspiration : Don't sell yourself short -- Imagination : Using your imagination -- Self-discipline : Going for the gold -- Civility : Competition -- Cooperation : Studying together -- Honesty : Plagiarism -- Initiative : Obstacles to initiative -- pt. 2. The circumstances of learning. Who teaches you : How should teachers help you? ; Teachers are human, too ; Knowledge and moral good -- What you learn : The arts and sciences ; Choosing your courses -- How you learn : Grades -- From school to college : Is knowledge all? -- Some final thoughts -- What to do : Listen and observe! ; Reflect! ; Question! ; Explore! ; Adapt! ; Apply what you learn! ; Share your knowledge! ; Admit ignorance! ; Accept uncertainty! ; Learn anytime! ; Learn anywhere! ; Evaluate yourself!
Print version record.
JSTOR
Keywords: Learning; Study skills; Learning, Psychology of; College student orientation; Learning; Apprentissage; Étude -- Méthodes.; Psychologie de l'apprentissage.; Étudiants -- Orientation; EDUCATION -- Higher; College student orientation; Learning; Learning, Psychology of; Study skills; Leerstrategieën.; Studievaardigheden